Using a Student-Centered Approach to Feedback that Fosters Active Learning and Knowledge Construction - M. Carolina Orgnero; Sandy Bell (Adult Education Research Conference, 2008)
The purpose of this roundtable is to invite participants to examine the ways and extent to which their methods of engaging students in feedback processes support a student-centered approach to feedback. The authors will introduce a research-based model of feedback that analyzes how college students apply feedback to their writing.
Keywords: student-centered approach; feedback; experiential learning; writing